THE INFLUENCE OF PARENTS IN APPLYING THE PROBLEM BASED INSTUCTION LEARNING MODEL IN IMPROVING THE LEARNING OF INDONESIAN LANGUAGE OUTOMES OF FOURTH GRADE STUDENTSAT SD NEGERI 153025 SIMARGARAP PASARIBU TOBING SUMATERA UTARA - Ben Gurion Purba (Jurnal Scientia, 2022)
Acknowledgements the researcher would like to express gratitude to God Almighty who has bestowed His love and Grace so that this research report can be completed properly. In this report, the researcher determines the title, namely the influence of parents in the Problem Based Instruction learning of Indonesian Language, model in improving the learning outcomes of fourth grade students at SD Negeri 153025 Simargarap, North Sumatera. The researcher would like to thank those who have helped in the preparation of this research, especially Rector of UHKBPNP, Dean of FKIP, Head of Study Program and employees who have helped the smooth implementation of the researches. Finally,the researcher asks for criticism and suggestion from readers for the improvement of the next step. Researcher hope that this research can have a positive impact of the development of increasing human resources.